From demands for free and fair elections to electoral reform – the dialogue between government and opposition in Serbia in 2019 - Jovanović, Milan (Sociološki pregled, 2021)
This article analyses the context that led to a dialogue on electoral conditions between the Serbian government and the opposition by applying the methodological matrix of standards for “free and fair” elections as defined by international organizations. Serbian electoral law has implemented international standards, but all electoral cycles have shown a certain level of irregularities that call into question the integrity of a number of electoral processes in the 2012–2017 interval. Two rounds of interparty dialogue produced only partial results. By amending a number of laws, certain election procedures were improved, but they remained in the shadow of unresolved crucial problems. Public broadcasting services remained closed to opposition parties and alternative policies, and the pressure on voters remained present. Instead of improving election conditions, major electoral reform was carried out. The electoral threshold was lowered from 5% to 3%. This form of electoral engineering carried out by the government did not diminish the boycott of the opposition, but it brought about significant changes in the electoral system, the effects of which were felt in the next elections. The epilogue of the dialogue was a boycott of the election by a part of the opposition parties, a politically unrepresentative parliament, and the Serbia’s return to the ranks of authoritarian, hybrid regimes in index bases that measure the quality of democracy. The announcement of early elections immediately after the constitution of the national parliament and a new round of dialogue on electoral conditions show that the problem of electoral integrity is still waiting for a solution.